The Chronographia of George the Synkellos and Theophanes The Ends of Time in Ninth-Century Constantinople - Torgerson, Jesse W. (Brill, 2022)
The ninth-century Chronographia of George the Synkellos and Theophanes is the most influential historical text ever written in medieval Constantinople. Yet modern historians have never explained its popularity and power. This interdisciplinary study draws on new manuscript evidence to finally animate the Chronographia's promise to show attentive readers the present meaning of the past. Begun by one of the Roman emperor's most trusted and powerful officials in order to justify a failed revolt, the project became a shockingly ambitious re-writing of time itself-a synthesis of contemporary history, philosophy, and religious practice into a politicized retelling of the human story. Even through radical upheavals of the Byzantine political landscape, the Chronographia's unique historical vision again and again compelled new readers to chase after the elusive Ends of Time.